Leukocytosis and neutrophilia as independent prognostic immunological biomarkers for clinical outcome in the CAO/ARO/AIO‐04 randomized phase 3 rectal cancer trial. Issue 8 (2nd April 2019) - Diefenhardt, Markus; Hofheinz, Ralf‐Dieter; Martin, Daniel; Beißbarth, Tim; Arnold, Dirk; Hartmann, Arndt; von der Grün, Jens; Grützmann, Robert; Liersch, Torsten; Ströbel, Philipp; Grabenbauer, Gerhard G.; Rieger, Michael; et al.
Abstract : Peripheral blood leukocytosis and neutrophilia reflect cancer inflammation and have been proposed as prognostic immunological biomarkers in various malignancies. However, previous studies were limited by their retrospective nature and small patient numbers. Baseline peripheral blood leukocytes, neutrophils, hemoglobin, platelets, lactate dehydrogenase and carcinoembryonic antigen (CEA) were correlated with clinicopathologic characteristics, and clinical outcome in 1236 patients with rectal cancer treated with 5‐FU‐based preoperative chemoradiotherapy (CRT) alone or with oxaliplatin followed by surgery and adjuvant chemotherapy within the CAO/ARO/AIO‐04 randomized phase 3 trial. Multivariable analyses were performed using Cox regression models. After a median follow‐up of 50 months, baseline leukocytosis remained an independent adverse prognostic factor for disease‐free survival (DFS; HR 1.457; 95% CI 1.163–1.825; p = 0.001), distant metastasis (HR 1.696; 95% CI 1.266–2.273; p < 0.001) and overall survival (OS; HR 1.716; 95% CI 1.264–2.329; p = 0.001) in multivariable analysis. Similar significant findings were observed for neutrophilia and high CEA levels. Conversely, treatment‐induced leukopenia correlated with favorable DFS ( p = 0.037), distant metastasis ( p = 0.028) and OS ( p = 0.012). Intriguingly, addition of oxaliplatin to 5‐FU CRT resulted in a significant DFS improvement only in patients with neutrophilia and leukocytosis ( p = 0.028 and p = 0.002). Our findings have important clinical implications and provide high‐level evidence on the adverse prognostic role of leukocytes and neutrophils, and the impact of chemotherapy in the context of these biomarkers. These data could help guide patient stratification and should be further validated within prospective studies. Abstract : What's new? Cancer often causes an inflammatory response, recruiting leukocytes and neutrophils to the tumor site where they hinder anti‐cancer treatments. Here, the authors asked how leukocytosis and neutrophilia affect outcomes in rectal cancer. Unlike previous studies, which have been retrospective, this study examined a large cohort of patients within a phase 3 clinical trial. They found that baseline leukocytosis and neutrophilia independently predicted poor outcomes, including distant metastasis and shorter survival. Treatment‐induced leukopenia, meanwhile, correlated with better outcomes. Adding oxaliplatin to standard chemoradiation improved disease‐free survival only in those patients with leukocytosis & neutrophilia. These findings could lead to improved personalized treatments.